Pengaruh Penggunaan E-Arsip Elektronik terhadap Produktivitas Pegawai Sekretariat Daerah Kabupaten Aceh Barat - Fitrian, Uci; Jalil, Ivon (Regress: Journal of Economics & Management, 2023)
This article aims to determine the effect of the use of electronic e-archives on the productivity of the employees of the West Aceh District Secretariat. Electronic archives can reduce the level of paper usage and also reduce the risk of leakage of confidential office documents. With the implementation of the use of electronic e-files, it can be a factor driving the productivity of working employees. There are a lot of documents managed by the West Aceh Secretariat Office or more precisely in the general section every day such as staff reviews, absences, incoming letters, outgoing letters or other documents that require good archive management so that they can be arranged neatly, even though they still use the e-system. -electronic archives continue to experience problems such as a network that is not smooth in the general section of the West Aceh Regional Secretariat. This type of research is associative using primary data sources from secondary data. The sample in this study were 62 employees using the slovin formula. The sampling technique of this study used a proportionate stratified random sampling technique. The data analysis method used is simple linear regression. The results of this study indicate that partially there is a significant influence between the use of electronic e-archives on employee productivity, with a significant value of 0.000. Therefore it can be concluded that the alternative hypothesis statement (Ha) from the use of electronic e-archives has a positive and significant effect on employee productivity at the Regional Secretariat of West Aceh Regency, is accepted.